Provenance of fine-grained sedimentary rocks derived from Rb-Sr and Sm-Nd analyses: the example of the Santa Maria Formation (Triassic, Parana Basin, Southern Brazil) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
In this work, the Rb-Sr and Sm-Nd methods were applied to fine-grained sedimentary rock samples of the Santa Maria Formation (Triassic, Paraná Basin) in order to have provenance information. The Sm-Nd, although being considered as a new technique when applied to sedimentary rocks is an important parameter to the determination of potential source rocks. The acquired information with the Sm-Nd method and the integration with Rb-Sr data allowed to propose the reconstruction of the source areas concerning Santa Maria Formation. The results are fundamental to improve these methodologies when applied in sedimentary rocks.
Keywords: Sedimentary rocks; Rb-Sr methodology; Sm-nd methodology; Provenance